Estimating ethnic and national identities' importance amongst immigrants Iranian tribes - Cheheltani, Maryam; Deuraseh, Nurdeng @ Nurdeen; Ahmad, Zaid; Sabra, M. S. (Penerbit Universiti Pertahanan Nasional Malaysia, 2012)
Unappreciation and inattention to ethnic and national identity weakens unity, and this is a threat for national integrity and solidarity in culturally diverse societies. For this reason, governments and authorities try to strengthen national integrity through utilising ethnic and national identity. This study rates ethnic and national identities’ Importance amongst the minorities that settled in Tehran through a questionnaire. The city of Tehran as the capital and largest city in Iran is the main immigrant receiving areas in the country with 31% reception of immigrants. This research validated the results of the questionnaire through in-depth interview with Iranian cultural experts. Evidently, paying attention to ethnic and national identity establishes a tradition which will continue in history for the later generations. Moreover, attention to ethnic and national identity can stimulate people’s patriotism. This paper suggests that majority of Iranian groups shows interest in ethnic and national identities’ Importance. The interest of different tribes in their own ethnic and national identity can have tremendously important roles in implementing or not implementing major plans and long-term cultural programs.